Effectiveness of clustering system among form two students towards efficient classroom management / Athirah Shukri - Shukri, Athirah (Faculty of Education, 2011)
Smart schools, boarding schools, Maktab Rendah Sains MARA (MRSM), and some of the premier schools are now implementing a new arrangement of students in class. Students are seated in groups of 5 or 6 with a mentor for each group. This implementation is called the mentoring system that is expected to create positive atmosphere in the classroom. However, daily national schools with weak students, sometimes mixed ability students, are also implementing the same arrangement for students. Does this work effectively as it is effective to smart students? This study, therefore, will unpack what the literature says about the effectiveness of grouping the students in classroom and whether it influence students’ positive behavior in class regardless of their level of proficiency. The study will revolve around the Form 2 students of Sekolah Menengah Kebangsaan Pusat Bandar Puchong 1 (SMKPBP1) which has a variety of mixed ability students. In addition, this study will also come out with solutions to problems faced by teachers when students create problem due to the clustering of the students. The results and solutions are expected to become the guideline for other teachers.